Comparative efficacy of analgesic gel phonophoresis and ultrasound in the treatment of temporomandibular joint disorders - Sankar Narayanan Ramakrishnan; Nalini Aswath (Wolters Kluwer Medknow Publications, 2019)
Aim: The aim of this study is to determine the efficacy of phonophoresis in patients with temporomandibular disorders. Objective: To prove that phonophoresis could be an effective treatment modality in in patients with temporomandibular disorders. Procedure: Fifty patients diagnosed clinically and radiographically as temporomandibular disorder were randomly assigned into either of the two groups, namely, (Group A) plain ultrasound and (Group B) phonophoresis. Acoustic gel containing no pharmacological agent was applied in the ultrasound group, whereas a gel containing aceclofenac was applied in the phonophoresis group. Each group was treated three times a week for 2 weeks. The assessment of pain and inflammation both before and after treatment were done using the visual analog scale (VAS) and Creactive protein (CRP). Results: Intergroup comparison was done and analyzed statistically using independent ttest. Intragroup comparison was done using paired ttest. A significant difference in VAS scores and CRP levels before and after treatment were seen within both ultrasound phonophoresis PH groups. No significant difference was noted statistically between ultrasound and phonophoresis group. Conclusion: The results of this study suggests that though plain ultrasound as well as phonophoresis with aceclofenac gel are effective in the management of temporomandibular disorders. Phonophoresis was found be slightly superior as evident in VAS scores and CRP levels though not statistically significant.